Decadentism and Symbolism in Valle-Inclán’s El Yermo de las almas and their projection on XIX finisecular art (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
The purpose of this article is to analyse the decadent symbols on one Valle-Inclán symbolist’s pieces: El yermo de las almas. The project is divided in two sections: first of all, symbols on the atmosphere, connected to Maeterlinck literature. On the other hand, the female treatment, the decadent beauty as illness apology. However, we won’t stop in textual facts because it has been studied by the Valle-Inclán criticism. The emphasis of this project is to establish analogies with Spanish decadents’ modernism. After all, atmosphere and characters are analysing on their resemblance with most of the relevant paintings. The artist that will be analysed are Santiago Rusiñol, Ramón Casas, Anglada Camarasa o Zuloaga. To sum up, we will show Valle-Inclán artistic skill on his pieces, which seem pictures.Keywords. Finisecular art; decadent; illness; painting; symbols.
Keywords: Finisecular art; decadent; illness; painting; symbols.